أثر التوجه بالسوق في أداء المنظمة"دراسة مسحية على مراكزSyriatel& MTN في محافظة طرطوس" - ابراهيم, حسين; علي, سليمان; يوسف, علام (Latakia University Journal - Economic and Legal Sciences Series, 2014)
تواجه منظمات الأعمال تحديات كبيرة تؤثر في أدائها، وخاصةً أنها تمارس نشاطها في بيئة تتسم بعدم الاستقرار. هدفت الدراسة إلى معرفة أثر التوجه بالسوق في أداء المنظمة، من خلال دراسة مسحية على مراكز Syriatel&MTNفي محافظة طرطوس، وقد تم الحصول على البيانات من خلال استبانة مصممة لقياس التوجه بالسوق، كذلك تضمنت الاستبانة مجموعة أسئلة خاصة بقياس المتغيرات البيئية، بوصفها عوامل داعمة لاستراتيجية التوجه بالسوق،تم توزيع الاستبانة على العاملين في المنظمات محل الدراسة وتم الاعتماد على برنامج التحليل الإحصائي SPSS. أظهرت الدراسةوجود علاقة إيجابية ذات دلالة إحصايئية بين (التوجه بالسوق، المتغيرات البيئية) وأداء المنظمةعموماً، إذ بلغت قيمة معامل الارتباط بين المتغيرات المستقلة والمتغير التابع 73%، ومعامل التحديد 53.2%، وذلك عند درجة ثقة 95%، كذلك أظهرت الدراسة أن الاضطرابات التكنولوجية كأحد عناصر المتغيرات البيئية تؤثر سلباً على أداء المنظمات محل الدراسة، فيما تؤثر كل من توليد الاستخبارات واضطرابات السوق تأثيراً إيجابياً في أداء المنظمات محل الدراسة. Organizations face significant challenges affecting their performance, especially as they operate in an unstable environment. This study aims to investigate the effect of market orientation on organization‘s performance, through a surveycovering Syriateland MTN Centers in TartousGovernorate. This study's data have been collected through a questionnaire designed to measure market orientation and environmental variables. The SPSS program is used for obtaining results. This research shows a positive relationship between market orientation and environmental variables and the organization’s performance in general. The value of the correlation coefficient between the independent variables and the dependent variables is 73%, and the coefficient of determination is 53.2% when the degree of confidence is 95%. This study also shows that technological turbulence, as a component of environmental variables, has a negative effect on organization‘s performance, whereas both intelligence generation and market troubles have a positive effect on organization‘s performance.